PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT SEGARA TIMBER DI SAMARINDA - Romi Romi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
Occupational safety and health is important for companies that want to improve thei employees work produktivity. PT Segara Timber is one of the industry companies that relies heavily on the productivity of its employees work to meet the demands of the market in addition to achieving profit. However, the productivity of employees at PT Segara Timber in Samarinda is considered as not maximally due to some ongoing accident.This research aims to determine the impact of occupational safety and health to the productivity of PT Segara Timber employees in Samarinda. Safety (X1), and occupational health (X2) are used as independent variables while the emplyee’s work productivity (Y) becomes a dependent variable. Primary data is obtained by conducting interviews to 90 respondents using questionnaires. Secondary data is obtained by conducting field observations. Data was analyzed using multiple linear regression techniques with the help of SPSS version 23 statistical software.The results showed that occupational safety and helath variables were simultaneously influential to the employee’s work productivity at PT Segara Timber in Samarinda.Advice on PT Segara Timber, should be able to maintain and improve the implementation of occupational helath and safety indicators so that employees work productivity can increase.